Detection of Enterococcus avium in a case of urinary tract infection and haematuria. Issue 5 (16th May 2022) - Abo-Zed, Abdelrhman; Hegazy, Shaymaa; Phan, Tung
Abstract : Enterococci have been recognized as major pathogens causing nosocomial and community-acquired infections. The emergence of antimicrobial-resistant enterococci is one of the major public health challenges worldwide. While many enterococcal species have been identified, Enterococcus avium is rarely detected in humans. Here we present an interesting case of urinary tract infection and haematuria involving E. avium in a 72-year-old patient. The patient underwent antibiotic therapy and surgical procedures with excellent improvement. This case report highlights the important role of E. avium in clinical settings.